Firefighting Water Tanker Commuting Accident: Case report on why it happened and how to manage - Rosnah Ismail; Norfaqihah Mohtar; Nor Hisham Mohammad; Jamri Masran; Mohammad Paisal Adam; Rizal Abdul Manaf (ACHSM, 2024)
Road traffic accidents represent a significant global public health concern, and Malaysia is no exception. Within the Fire and Rescue Department of Malaysia (FRDM), similar issues have had detrimental impacts on health, financial loss, and service disruptions from 2016 to 2021. These challenges were highlighted by a recent accident involving a water tanker during a road test, described in this study according to qualitative data from the FRDM accident investigation report. The investigation revealed that human factor, as the active failure, was the primary cause of the accident. Response errors stem from a cascade of latent conditions initiated by inadequate resource management (i.e. provision of training and budget allocation). To address these challenges, the FRDM should adopt a comprehensive approach to address both latent conditions and active failures. This comprehensive approach ensures that both immediate concerns and root causes are addressed, leading to sustained improvements in safety and operational performance.